2010
DOI: 10.1111/j.1525-1594.2010.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Evaluation of Platelet Activation Induced by a Bioprosthetic Heart Valve

Abstract: It is known that bioprosthetic heart valves (BHVs) have better hemodynamics and lower thromboembolic events compared with their mechanical counterparts; however, patients implanted with BHVs still face the potential of such complications. The risk of a clinical thromboembolism is on average 0.7% per year in patients with tissue valves in sinus rhythm. In this study, we developed a computational fluid dynamic (CFD) model of a BHV implanted in an aortic root and investigated the BHV-induced platelet activation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…In a previous study, we observed a similar fold and high-velocity jet near the base of a bovine-pericardial bioprosthetic valve. 29 Our findings from Scenario 2 were consistent with those of Dwyer et al, who reported a 1.65 m/s peak flow through a normal TAV at systole, and reported a wide central flow region. 11 The change in jet velocity following TAV intervention resulted in peak wall shear stress on the ascending aorta being reduced from 105 Pa down to 38 Pa for Scenario 1 and to less than 1 Pa for Scenario 2.…”
Section: Impacts Of Tav On Aortic Flowsupporting
confidence: 94%
“…In a previous study, we observed a similar fold and high-velocity jet near the base of a bovine-pericardial bioprosthetic valve. 29 Our findings from Scenario 2 were consistent with those of Dwyer et al, who reported a 1.65 m/s peak flow through a normal TAV at systole, and reported a wide central flow region. 11 The change in jet velocity following TAV intervention resulted in peak wall shear stress on the ascending aorta being reduced from 105 Pa down to 38 Pa for Scenario 1 and to less than 1 Pa for Scenario 2.…”
Section: Impacts Of Tav On Aortic Flowsupporting
confidence: 94%
“…(10) alternatively. This has been used in several computational studies to calculate AP [9, 1, 133]. It should be noted however that for incompressible flow, σν=2μeF, and the two measures provide equivalent results.…”
Section: Tracking Cellular Damagementioning
confidence: 99%
“…It should be noted however that for incompressible flow, σν=2μeF, and the two measures provide equivalent results. Some experimental studies have suggested that stress and exposure time should not be “weighted equally,” but AP is better expressed as a power law of stress and exposure time [53, 2, 55, 106], which has been applied in several computational studies [9, 1, 102, 153, 132, 133, 12, 93]. …”
Section: Tracking Cellular Damagementioning
confidence: 99%
See 1 more Smart Citation
“…For example, computational models have predicted the effect of bone marrow stem cell transplantation on fibrosis in the cardiomyopathy associated with Chagas disease (Galvao et al 2008) or platelet activation after implantation of a bioprosthetic heart valve (Sirois and Sun 2010). The McCulloch group has published diverse computational models to study cardiac behavior, ranging from a model of focal myofibril disarray to represent regional septal dysfunction as seen in hypertrophic cardiomyopathy (Usyk et al 2001), to the effect of biventricular pacing on left ventricular function (Kerckhoffs et al 2009) and the influence of myosin regulatory proteins on myosin kinetics (Sheikh et al 2012).…”
Section: Computationalmentioning
confidence: 99%